Happy photocatalysts and unhappy photocatalysts: electron trap-distribution analysis for metal oxide-sample identification. Issue 2 (2nd December 2021) - Ohtani, Bunsho; Takashima, Mai
Abstract : An attempt to identify inorganic solids, such as metal oxides, using ERDT (energy-resolved distribution of electron traps)/CBB (conduction-band bottom) patterns, measured by reversed double-beam spectroscopy, as a "fingerprint" is introduced. Abstract : A strange story, including a new concept of identification of inorganic solid materials and of photocatalyst design, is told here. Why is it that solid materials have not been identified, while organic chemists are required to identify their organic compounds for publication of a report? What is the meaning of identification? Why is it almost impossible to identify inorganic solids? Is it possible to identify an inorganic solid by using a certain fingerprint? Can energy-resolved distribution of electron traps (ERDT) patterns be fingerprint of solid materials? What do ERDT/CBB (conduction-band bottom) patterns tell us about the photocatalytic activity of titania samples?